Content validity of the SOS-WRIST questionnaire for timely identification of wrist overuse in young athletes. Issue 3 (3rd July 2019) - Kox, L. S.; Kuijer, P. P. F. M.; Opperman, J.; Kerkhoffs, G. M. J. J.; Maas, M.; Frings-Dresen, M. H. W.
ABSTRACT: Objectives : Young athletes do not always seek medical help for overuse wrist injuries, risking invalidating long-term consequences resulting from late diagnosis. This study aimed to develop a questionnaire to identify overuse wrist injuries in young athletes. Methods : According to the COnsensus-based Standards for the selection of health Measurement INstruments (COSMIN) criteria, items were collected from literature and 6 focus groups of sports physicians and of young athletes with (previous) overuse wrist injuries. An expert panel and 40 Delphi study participants performed item reduction. Young athletes evaluated comprehensiveness during interviews and English translation was performed according to linguistic validation guidelines. Results : In total 323 items were generated and 110 were marked important by focus group participants. The resulting questionnaire consists of 18 multiple-choice questions about wrist pain during sports (e.g. pain during training, skipping training sessions/elements) and daily life activities (e.g. writing, turning a key), and other symptoms (e.g. reduced strength, swelling). Conclusion : The SOS-WRIST questionnaire for identification of overuse wrist injuries in young athletes has good content validity. It can be used to promote awareness and timely treatment of overuse wrist injuries in young athletes.